A meta-analysis of blood lead levels in India and the attributable burden of disease. (December 2018) - Ericson, Bret; Dowling, Russell; Dey, Subhojit; Caravanos, Jack; Mishra, Navya; Fisher, Samantha; Ramirez, Myla; Sharma, Promila; McCartor, Andrew; Guin, Pradeep; Taylor, Mark Patrick; Fuller, Richard
Abstract: Multiple studies in India have found elevated blood lead levels (BLLs) in target populations. However the data have not yet been evaluated to understand population-wide exposure levels. We used arithmetic mean blood lead data published from 2010 to 2018 on Indian populations to calculate the average BLLs for multiple subgroups. We then calculated the attributable disease burden in IQ decrement and Disability Adjusted Life Years (DALYs). Our Pubmed search yielded 1066 articles. Of these, 31 studies representing the BLLs of 5472 people in 9 states met our study criteria. Evaluating these, we found a mean BLL of 6.86 μg/dL (95% CI: 4.38–9.35) in children and 7.52 μg/dL (95% CI: 5.28–9.76) in non-occupationally exposed adults. We calculated that these exposures resulted in 4.9 million DALYs (95% CI: 3.9–5.6) in the states we evaluated. Population-wide BLLs in India remain elevated despite regulatory action to eliminate leaded petrol, the most significant historical source. The estimated attributable disease burden is larger than previously calculated, particularly with regard to associated intellectual disability outcomes in children. Larger population-wide BLL studies are required to inform future calculations. Policy responses need to be developed to mitigate the worst exposures. Highlights: Blood lead levels remain elevated in India despite the phase-out of leaded petrol. Lead exposure results in a significant burden of disease in India. Currently, lead-attributable DALYs are likely underestimated in children. Sources of lead exposure need to be better investigated and isolated in India.